Power relations in the management of the Sisik Naga Hills forest from a political ecology perspective - Isna Hanny Puspitaningtyas (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Forest governance in Indonesia faces a fundamental paradox. 95.5 million hectares of forest are claimed as critical conservation assets, yet 70% of the area is managed through centralized institutions. This situation tends to marginalize local communities. This study examines power relations in state forest management in the Sisik Naga Hills, Purbalingga, Central Java. Forest management in this area is formally participatory, but upon closer examination, it harbors structural inequalities. This study aims to analyze the power mechanisms operating through the Forest Village Community Institution (LMDH) and explore the ecological consequences of exclusionary management practices. Methods: This qualitative research uses a desk study method. Political ecology is used as the research framework. Data include policy documents, academic publications, and institutional reports related to social forestry and state forest governance. Thematic analysis was conducted to map forest ownership structures, local institutional dynamics, and exclusionary mechanisms in decision-making. Findings: The results found that the conversion of protected forests into cardamom plantations in Karangmoncol resulted in an escalation of disasters and material losses. The ambiguity of zoning boundaries and the dominance of local elites create blind spots that exclude community ecological knowledge. Conclusion: This study concludes that the absence of explicit conflict is not an indicator of balance, but rather a product of power relations that have been naturalized through formal procedures. Novelty/Originality of this article: This study extends the political ecology literature by showing that power does not always operate through open conflict, but rather through bureaucratic mechanisms that appear neutral but systematically benefit dominant actors in areas that have been marginalized in national forestry discourse.